THE THERMODYNAMICAL PROPERTIES OF MELTS OF SYSTEM Al – La – Si - Судавцова, В.; Шаркіна, Н.; Кудін, В.; Матейко, І.; Шевченко, М. (Proceedings of National Aviation University (archive), 2012)
An aluminium, rare-earth metals (La) and their alloys, is used as deoxidants, desulfurizers and modifiers of steels. In addition, the alloys of aluminium with silicon (silumins) are very widely used in the different areas of industry. Therefore an aim hired was the use of reliable values of thermodynamics properties of the systems of Al – La, Al – Si, La – Si which analogical properties of triple alloys from Al – La – Si were expected. Experimental researches of thermo-chemical data (the partial enthalpy of mixing of silicon is in melts of Al – Si,) for the systems of Al – La, Al – Si and La – Si was conducted by the method of isoperibelical calorimetry. States of activity of components of melts expected from a diagram Al – Si at 1800 K comport with the most known literary data. Energies of Gibbs mixing of melts of Al – La were modelled on the described methodology (Gsurplus = – 25 kJ/mol at xAl = 0,37). With the use of the obtained data thermodynamics properties of the triple system Al – La – Si are expected on the formulas of Cohler and Bonier-Cabo. It is set, that between the experimental and expected data there is good correlation